Production and Utilization of Moodle-Based e-Learning to Enhance Higher-Order Thinking Skills with the STEM Approach - Restanti, Mida Ayu; Hasnunidah, Neni; Suyatna, Agus; Abdurrahman, Abdurrahman (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study aimed to develop a Moodle-based e-learning platform with a valid, practical, and effective STEM approach to enhance Higher-Order Thinking Skills (HOTS). The research methodology employed for development purposes was the ADDIE model, consisting of five distinct phases: Analysis, Design, Development, Implementation, and Evaluation. The selection of research subjects for the field trial was conducted through cluster random sampling, wherein experimental and control classes were chosen. The experimental class utilized a Moodle-based e-learning solution for instructional purposes, while the control class adhered to traditional learning methods. Data were collected using validated questionnaires and written tests. The findings indicated that the Moodle-based e-learning products with a STEM approach are effective in enhancing students’ higher-order thinking skills. This was evident from the average n-Gain gain falling in the "medium" category at 0.62 and an effect size also in the "medium" category at 0.43. Student responses to the Moodle-based e-learning were very positive. Based on the research findings, the researcher offers some recommendations. Teachers aiming to utilize this product could enhance its effectiveness by incorporating additional platforms into their learning activities and resources. Additionally, other researchers interested in advancing further studies can introduce problem-solving activities to stimulate higher-order thinking skills (HOTS) in everyday situations. In conclusion, the Moodle-based STEM e-learning product is effective in enhancing students' HOTS.